2007
DOI: 10.1177/0146167206297402
|View full text |Cite
|
Sign up to set email alerts
|

Why Individuals Protest the Perceived Transgressions of Their Country

Abstract: The present research examined emotions as predictors of opposition to policies and actions of one's country that are perceived to be illegitimate. Two studies investigated the political implications of American (Study 1) and British (Study 2) citizens' anger, guilt, and shame responses to perceived harm caused by their countries' occupation of Iraq. In both studies, a manipulation of pervasive threat to the country's image increased participants' shame but not guilt. The emotions predicted political action int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
426
2
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(470 citation statements)
references
References 31 publications
23
426
2
10
Order By: Relevance
“…In the few examples in which the research included prosocial options, moral outrage (anger provoked by the perception that a moral standard has been violated; see Batson et al 2007) correlated substantially with both participants' assignment of perpetrator punishment and victim compensation (Darley and Pittman 2003;Lotz et al 2011a, b). In a similar vein, Vitaglione and Barnett (2003) found that empathic anger was positively related to both helping a victim and punishing a perpetrator; Montada and Schneider (1989) and Wakslak et al (2007) found that moral outrage correlates with prosocial activities such as donating money, signing petitions, and supporting social projects in favor of the disadvantaged; and Iyer et al (2007) suggested that anger aimed at the ingroup predicted compensation to an outgroup. Although all these findings are suggestive of a relationship between third-party anger and prosocial behavior, none of these studies included manipulations of anger.…”
Section: First-party and Third-party Angermentioning
confidence: 88%
See 2 more Smart Citations
“…In the few examples in which the research included prosocial options, moral outrage (anger provoked by the perception that a moral standard has been violated; see Batson et al 2007) correlated substantially with both participants' assignment of perpetrator punishment and victim compensation (Darley and Pittman 2003;Lotz et al 2011a, b). In a similar vein, Vitaglione and Barnett (2003) found that empathic anger was positively related to both helping a victim and punishing a perpetrator; Montada and Schneider (1989) and Wakslak et al (2007) found that moral outrage correlates with prosocial activities such as donating money, signing petitions, and supporting social projects in favor of the disadvantaged; and Iyer et al (2007) suggested that anger aimed at the ingroup predicted compensation to an outgroup. Although all these findings are suggestive of a relationship between third-party anger and prosocial behavior, none of these studies included manipulations of anger.…”
Section: First-party and Third-party Angermentioning
confidence: 88%
“…An additional reason for having overlooked prosocial consequences of anger could be the dominant theoretical focus on negative consequences of anger, most notably punishment. Previous studies that did look at positive or prosocial effects of anger were mainly correlational in nature, were inconsistent in the operationalization of anger (e.g., Iyer et al 2007;Montada and Schneider 1989;Wakslak et al 2007), lacked a simultaneous measure of both compensatory and punitive measures (as in third-party punishment studies), or the compensatory and punitive measures were not costly (e.g., Adams and Mullen 2014). Finally, studies that did include positive consequences typically did not directly measure situational, state anger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basándose en la idea de que las categorizaciones sociales llevan a la gente a internalizar los atributos asociados con su categoría, Doosje et al (1998) supusieron que las personas experimentarían en forma vicaria un sentido de culpa compartida respecto de las acciones negativas de su endogrupo. En concordancia con sus predicciones, diversos estudios han demostrado que los sentimientos de culpa colectiva motivan la reparación intergrupal en distintos contextos Doosje et al, 1998;Iyer, Schmader & Lickel, 2007). A ello se ha sumado el rol que tiene la vergüenza colectiva en los procesos de reparación.…”
Section: Emociones Intergrupales Asociadas Al Perdón Y La Reparaciónunclassified
“…El patrón de resultados obtenido confirma parcialmente lo que hipotetizamos, demostrando que el rol de los grupos en el conflicto (víctima o perpetrador) es relevante. asoció con el perdón en los dos grupos -además de asociarse con la reparación en el grupo de derecha-, mientras que la culpa se relacionó con la reparación, también en ambos grupos, y con el perdón, en el caso de la izquierda Doosje et al, 1998;Iyer, Leach & Crosby, 2003;Iyer et al, 2007;Lickel et al, 2005;Wohl & Branscombe, 2005). El hecho de que la empatía intergrupal se asocie consistentemente con el perdón es coherente con estudios previos que han mostrado que la capacidad para comprender la perspectiva con que la otra parte experimentó el conflicto es importante para aceptar la posibilidad de perdonar al exogrupo Dovidio et al, 2004;Finlay & Stephan, 2000;Noor, Brown & Prentice, 2008).…”
Section: Conclusionesunclassified